1991
DOI: 10.1097/00006676-199107000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Various Sialylated Carbohydrate Antigens in Malignant and Nonmalignant Pancreatic Tissues

Abstract: The expression of six sialylated carbohydrate antigens (CA19-9, CA-SO, SLEX, SLX, DU-PAN-2, was examined in malignant and nonmalignant pancreatic tissues using an immunohistochemical method to elucidate the characteristics of these carbohydrate antigens as tumor markers. All carbohydrate antigens except for sialyl SSEA-I (SLX, 52.4%) were expressed in more than 80% of the pancreatic cancer. CA19-9 and CA-50, belonging to type I blood group antigens, and DU-PAN-2 and ST-439 were localized predominantly in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…In chronic pancreatitis tissues, cytoplasmic staining was observed in addition to apical staining, whereas only apical staining was seen in normal pancreatic tissues. The correlation between the disturbed antigen polarity and serum level was reported to be more prominent in pancreatic cancer tissues (Satomura et al, 1991). However, a different study demonstrated no such relationship in colorectal cancer tissues for CEA and CAl9-9 (Tabuchi et al, 1988).…”
Section: Ca242 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic pancreatitis tissues, cytoplasmic staining was observed in addition to apical staining, whereas only apical staining was seen in normal pancreatic tissues. The correlation between the disturbed antigen polarity and serum level was reported to be more prominent in pancreatic cancer tissues (Satomura et al, 1991). However, a different study demonstrated no such relationship in colorectal cancer tissues for CEA and CAl9-9 (Tabuchi et al, 1988).…”
Section: Ca242 Discussionmentioning
confidence: 99%
“…The mechanisms concerning the false serum elevation of tumour markers in chronic pancreatitis have been analysed by means of immunohistochemical study. Satomura et al (1991) reported that disturbed antigen polarity plays a significant role in the elevation of serum CA19-9 levels. In chronic pancreatitis tissues, cytoplasmic staining was observed in addition to apical staining, whereas only apical staining was seen in normal pancreatic tissues.…”
Section: Ca242 Discussionmentioning
confidence: 99%
“…Non-specific cytoplasmic staining with either CEA or CA19-9 has previously been demonstrated in both the normal and inflamed pancreatic ductal epithelium [35][36][37] . Performance was poor for all the markers when used as indicators for the absence of malignancy (alone or in various parallel combinations of up to four markers) as demonstrated by low NPVs and non-significant NLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Lectins and glycan-binding antibodies have been used extensively in immunohistochemistry, for example in studies to examine the tissue distribution in pancreatic tumors of certain blood group carbohydrates (4,5). Lectins have been valuable in immunoaffinity electrophoresis and blotting methods to identify cancer-associated glycan variants on major serum proteins such as ␣-fetoprotein (6), haptoglobin (7,8), ␣ 1 -acid glycoprotein (9), and ␣ 1 -antitrypsin (10).…”
mentioning
confidence: 99%